Parental Monitoring: A Reinterpretation - Stattin, Häkan; Kerr, Margaret (Child development, 2000)
Monitoring (tracking and surveillance) of children's behavior is considered an essential parenting skill. Numerous studies show that well-monitored youths are less involved in delinquency and other normbreaking behaviors, and scholars conclude that parents should track their children more carefully. This study questions that conclusion. We point out that monitoring measures typically assess parents' knowledge but not its source, and parents could get knowledge from their children's free disclosure of information as well as their own active surveillance efforts. In our study of 703 14-year-olds in central Sweden and their parents, parental knowledge came mainly from child disclosure, and child disclosure was the source of knowledge that was most closely linked to broad and narrow measures of delinquency (normbreaking and police contact). These results held for both children's and parents' reports, for both sexes, and were independent of whether the children were exhibiting probelm behavior or not. We conclude that tracking and surveillance is not the best prescription for parental behavior and that a new prescription must rest on an understanding of the factors that determine child disclosure.